DAMPAK POLA ASUH OTORITER PARENTIAL TERHADAP PERKEMBANGAN SOSIAL EMOSIONAL ANAK DI MASA GOLDEN AGE(Studi Kasus di Kota Cirebon) - Arib Mubarok; Muslihudin; Suklani (CV. ADIBA AISHA AMIRA, 2024)
The cases found in children in Cirebon City were children's disobedience towards their parents. Apart from disobedience, another thing is that children often play with gadgets every day to the point of ignoring their parents' orders, resulting in many parents adopting an authoritarian parenting style. This is what the researchers found in a community with a background in the middle of the city, namely Cirebon City. Parental parenting styles actually have a very central role in a child's development, but wrong parenting patterns will have a negative impact on a child's development and vice versa. Early childhood children usually cannot control their emotions, they will get angry easily, cry, be stubborn, scream, and sometimes even become violent. This research aims to determine 1) the impact of parental authoritarian parenting on the social emotionality of children during the golden age in Cirebon City, 2) the social emotional development of children during the golden age in Cirebon City, 3) factors that influence parental authoritarian parenting during the golden age age in Cirebon City. The method used in this research is descriptive qualitative. The data collection techniques used in this research are observation, interviews and documentation. Based on the research that has been conducted, there are results: 1) The Impact of Authoritarian Parenting Patterns: Many parents still apply authoritarian parenting patterns themselves. However, there are also some parents who use a democratic parenting style. 2) The development of social emotional intelligence in early childhood in Cirebon City is said to have several obstacles, such as children being hypnotized by gadgets so that the process of children's social emotional development is slightly disturbed. 3) There are several factors that influence the occurrence of authoritarian parenting patterns, including low education, low economic conditions and culture that is still attached to the environment.